Investigating Sustainable Practices in Hotel Industry-From Employees' Perspective: Evidence from a Mediterranean Island - Alipour, Habib; Safaeimanesh, Farzad; Soosan, Arezoo (Mdpi, 2019)
Although several studies have researched the hotel employees' environmental behavior, none has addressed the hotel employees' perception of their respective hotels' sustainability practices. This study aims to investigate the sustainable practices in four and five star hotels in a Mediterranean island by employing Global Sustainable Tourism Council (GSTC) hotel criteria indicators, indicators of sustainable development for tourism destinations (WTO), and the European Union's (EU) sustainability framework for the Mediterranean hotels-Nearly Zero -Energy Hotels (NEZEH), and global sustainable development goals (SDG) in the context of three dimensions: social, economic and environment. The sampled hotels claim that their operation system is conformed to sustainability principles with the aim of furthering their green agenda. In this study, we aim to investigate the validity and extent of this claim. About 290 (N = 290) employees in the specified hotels were surveyed. The measurement instruments were compiled based on sustainability indicators that encompassed addressing social, economic, and environmental dimensions. The research questions contextualized around four main themes: effective sustainability planning, maximizing social and economic benefits for the local community, enhancing cultural heritage, and reducing negative environmental impacts. For the statistical and data analysis, SEM (structural equation modeling) is used. Study revealed that employees are a legitimate and credible source of information about sustainability practices. It is also revealed that as going green is becoming a means toward branding, hotels are making efforts to implement a genuine sustainability practice. Study also indicated that the majority of employees validated the sustainability practices as genuine.
Keywords: tourism; tourism accommodations; sustainable development; sustainable practice; employee perception; north Cyprus